PELATIHAN PENULISAN BAHAN AJAR BAHASA INDONESIA BERGENRE TEKS BERBASIS KECAKAPAN HIDUP UNTUK GURU-GURU MA PROVINSI JAWA BARAT - Halimah, Halimah; Kurniawan, Khaerudin; Kusumah, Encep; Resmini, Novi (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2021)
The training of composing genre-based and life-skills-based materials for Indonesian language teaching aims to deal with students’ enormous future challenges. Therefore, this training allowed teachers to develop life-based Indonesian language teaching materials and to teach them to students. Methods to analyze the implementation are direct observation, interviews, and presentations during the program. This community service program concludes that: (1) most of the training participants gave positive responses about the significance of teaching materials developed, training implementation facilities, and instructor assessments, (2) the development of Indonesian language course modules and textbooks comprises printed, audio, visual, and multimedia materials, (3) the needs analysis of the Indonesian language teaching materials for Madrasah Aliyah is oriented to the needs of improving students' abilities regarding language, literature, and literacy, (4) alternative literature teaching materials for Madrasah Aliyah should contain examples of life-skills principles that participants should follow.